Interpreting and reporting clinical trials with results of borderline significance. (4th July 2011) - Hackshaw, Allan; Kirkwood, Amy
Abstract : Borderline significance in the primary end point of trials does not necessarily mean that the intervention is not effective. Researchers and journals need to be more consistent in how they report these results